Diseño y construcción de un aerogenerador experimental y modular para aplicación rural. - Cabrera González, Oscar Iván (2008)
The present instigation work heads like a solution measure before a world and national problem related with the global heating and with the use of the renewable energies using a source of alternative energy as it is the energy of the wind or eolic involving directly to the National University of Loja and in if to the Area of Energy and Industries and of the Natural Resources not Renewable. He thinks about the Design, Construction of an Experimental aerogenerador for Rural additional application to this a System of Acquisition of Environmental Data that allows the students to know a type of renewable and inexhaustible energy as it is that of the wind and to take advantage of the eolic potential with which it counts the county of Loja and also to know by means of monitoreo and presented in computer to the conditions climatic present in our means. The built aerogenerador is a very functional prototype and it can be transported places where general electricity was wanted since it is one it schemes very reliable and of good results. First one carries out the design and I calculate then from the in agreement aerogenerador to the power that was wanted to obtain, you selects the variables to measure and the type of in agreement sensor to each mensuration stops then to condition the signs and being presented by computer by means of a software Labview that allowed to be carried out our mensurations and the values to be presented in realtime. These data can be analyzed and presented. In the final part we carry out an economic valuation and of environmental, visual impact, social of our team with the obtained results.